PENGARUH MODEL PEMBELAJARAN MAKE A MATCH UNTUK PEMAHAMAN KONSEP KEKAYAAN ALAM PESERTA DIDIK KELAS IV SDN TANGGUL SIDOARJO - Zelda, Susmita Amelia Putri; Jannah, Novaria Lailatul (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2024)
This study aims to determine the effect of the make a match learning model for understanding the concept of natural resources material for fourth grade students of SDN Tanggul Wonoayu. This research is included in quantitative research. This quantitative research uses a pre-experimental design that uses the One Group pretest-posttest design method. The results of data analysis using the help of SPSS software 26 for windows. The results of pretest and posttest data processing calculated using SPSS show a 2-tailed sig value of 0.260 and 0.053. The significance results show more than 0.05. This means that the data is normally distributed. Therefore, the hypothesis test used is the paired sample t-test. The results of the paired sample t-test test obtained a significance value of 0.000 (0.000<0.005) then Ho is rejected and Ha is accepted. This means that the hypothesis states that there is an effect on understanding the concept of natural resources material between before and after being given the make a match learning model. The N-Gain test obtained a value of 56.9085 with a fairly effective category. It can be concluded that the influence of the make a match learning model for understanding concepts can improve the understanding of class IV students at SDN Tanggul